2010
DOI: 10.1094/mpmi-23-7-0962
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Barley–Deoxynivalenol Interaction: Evidence for a Role of Glutathione in Deoxynivalenol Detoxification

Abstract: Trichothecenes are a major group of toxins produced by phytopathogenic fungi, including Fusarium graminearum. Trichothecenes inhibit protein synthesis in eukaryotic cells and are toxicologically relevant mycotoxins for humans and animals. Because they promote plant disease, the role of host responses to trichothecene accumulation is considered to be an important aspect of plant defense and resistance to fungal infection. Our overall objective was to examine the barley response to application of the type B tric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
135
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(148 citation statements)
references
References 61 publications
9
135
0
Order By: Relevance
“…Similar studies have also preliminarily addressed the formation of DON3G in barley and durum wheat (Gardiner et al, 2010;.…”
Section: Natural Occurrence and Environmental Fatementioning
confidence: 82%
“…Similar studies have also preliminarily addressed the formation of DON3G in barley and durum wheat (Gardiner et al, 2010;.…”
Section: Natural Occurrence and Environmental Fatementioning
confidence: 82%
“…4). Previous studies on wheat and barley have established that genes encoding UGTs are up-regulated following fungal infection (Lemmens et al, 2005;Boddu et al, 2007;Gottwald et al, 2012) or DON application (Gardiner et al, 2010;Lulin et al, 2010). However, in several transcriptomic studies, overall differences in gene expression were partly due to their different genetic backgrounds between FHBresistant and -susceptible lines rather than differences in specific resistance loci (Jia et al, 2009).…”
Section: The Bradi5g03300 Ugt Is Involved In Root Tolerance To Donmentioning
confidence: 99%
“…The induction of jasmonate-regulated allene oxide synthase and 12-oxo-phytodienoic acid reductase (Gottwald et al, 2012;Kugler et al, 2013;Xiao et al, 2013), and the related metabolites linoleic and linolenic acids, jasmonates, and traumatic acid (Bollina et al, 2011;Kumaraswamy et al, 2011a), have been described as markers of quantitative resistance to FHB. Other common features were associated with defense responses such as the induction of b-1,3-glucanases, chitinases, and thaumatin-like proteins, the scavenging of reactive oxygen species, and xenobiotic detoxification by family 1 UDP-glycosyltransferases, glutathione S-transferases, cytochrome P450-monooxygenases, and transporter detoxification (Boddu et al, 2006;Golkari et al, 2007;Jia et al, 2009;Gardiner et al, 2010;Foroud et al, 2012;Kugler et al, 2013;Xiao et al, 2013). Other phenomena that have been linked to resistance to FHB include increased photosynthesis and carbohydrate metabolism involving chloroplast oxygen-evolving enhancer proteins, NAD(P) + -binding proteins, and the pentose phosphate pathway (Kugler et al, 2013;Zhang et al, 2013).…”
mentioning
confidence: 99%
“…A subsequent transcriptome study of this barley cv. Morex confirmed that genes encoding ABC transporters, UGTs, CYP450s and GSTs were responsive to pure DON (Gardiner et al 2010) and that overexpression of cystathionine β-synthase, a key enzyme for glutathione production, enhanced the conversion of DON to the less toxic derivative DON-glutathione in yeast.…”
Section: Genetic Loci Linked To Don Detoxificationmentioning
confidence: 80%